HUMOR IN FILM OF THE SUICIDE SQUAD (2021) BY JAMES GUNN - Hikma, Nurul; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to analyze the humor in the film The Suicide Squad 2021. The researchers focus on analyzing the techniques of humor used in the film and the function of humor itself. Currently, film is a work of art that is very popular among the public and also a very global entertainment industry. Many people watch and like the film itself based on its genre. The Suicide Squad 2021 film itself was written and directed by James Gunn. The story of this film is said to be full of colors and humor in it which can make the audience interested in watching it. In the techniques of humor, researchers use Berger's theory which according to him there are 45 techniques in creating humor. As for the function of humor using the theory of Nilsen. The method used in this research is descriptive qualitative method, which is a research method using qualitative data then described descriptively. This research shows that there is some amount of humor found in Film of The Suicide Squad 2021 by James Gunn based on the technique of making the humor itself. There are 65 research data found in the film of The Suicide Squad 2021 by James Gunn where there are 34 techniques of humor out of 45 techniques according to Athur Asa Berger and 11 other humors not found in the film. Based on its function, it has 15 psychological functions, 17 educational functions, 30 social functions and no physiological functions. There is humor that is found that is not included in Nilsen's theory but includes from the theory functions of Scheel (2017) which are 2 intrapersonal functions and 1 interpersonal function. Based on this research, it can be concluded that every humor created is based on the technique used and each humor has a different function.